The degeneration of upper and lower motor neuron from the perspective of clinical neurological examination and MRI-electromyography manifold detection in amyotrophic lateral sclerosis. Issue 1 (6th January 2021) - Jin, Jiaoting; Hu, Fangfang; Zhang, Qiuli; Chen, Qiaoyi; Li, Haining; Qin, Xing; Ji, Rui; Kang, Li; Dang, Yonghui; Dang, Jingxia
Abstract : Objective: The aim of this study was to explore the upper motor neurons (UMN) and lower motor neurons (LMN) degeneration in amyotrophic lateral sclerosis (ALS) from the perspective of the clinical neurological examination and MRI-electromyography manifold detection, respectively. Methods: The clinical data, cortical thickness of corresponding areas in different body regions in MRI and electromyography data were collected from 108 classical ALS patients. Results: The kappa value of UMN and LMN involvement signs in the bulbar region (0.31) was higher than that of the left upper limb (−0.13), right upper limb (−0.27), left lower limb (−0.05) and right lower limb (−0.08). The cortical thickness in the positive LMN damage group was thinner than that of the negative LMN damage group in the left head–face area ( P  < 0.05; Cohen's d  = 0.84); however, cortical thickness showed no significant differences in the right head–face, bilateral tongue–larynx, upper-limb, trunk and lower-limb areas between LMN-damage-positive and LMN-damage-negative groups. Conclusion: The degeneration of motor neuron could be independent through UMN and LMN levels. The degenerative process was not only confined to UMN and LMN levels but can also expand to white matter fiber tracts. Thus, the degeneration of UMN and LMN might be independent of the motor system's three-dimensional anatomy.